Testing of a novel IFAS-MBR process with co-precipitation - B. Rusten (IWA Publishing, 2021)
IFAS-MBR with co-precipitation, not yet commonly used in practice, will result in a very compact process for nutrient removal. The process, based on a combined pre- and post-denitrification IFAS process with membrane separation (IFAS-MBR), was tested in two parallel small-scale plants. Train A was operated with co-precipitation in order to achieve high removal of total P (TP). Train B, without co-precipitation, served as a control. Due to the coagulant (Al) addition, the concern was precipitation on the biofilm carriers in the aerobic reactor in Train A. A small internal air-lift pump proved to be very efficient in controlling biofilm thickness and removing excess biofilm mass as needed. A coagulant dose equivalent to an Al/TP molar ratio of 1.9 was necessary to achieve 99% TP removal and 0.10 mg TP/l in the effluent of Train A. Very good removal of total N was achieved in both trains. Train A had a biofilm nitrification rate of 0.65 g NH4-N/m2d at 12–13 °C and 5.2–5.6 mg O2/l. The tests demonstrated that an IFAS-MBR process with co-precipitation and an aerobic suspended biomass SRT of 5–10 days is feasible, and that all the performance goals set up for the full-scale plant were achieved. HIGHLIGHTS IFAS-MBR with co-precipitation and combined pre- and post-denitrification for removal of P and N from wastewater.; Removal of 95% COD, 80% N, 100% SS and 99% P at a dose of 1.9 mol Al/mol P.; Air-lift pump to control the biofilm biomass and optimize nitrification on the biofilm carriers in the IFAS reactor.; IFAS-MBR process worked well at suspended biomass aerobic SRTs of 5–10 d.;